Trends and health burden of hospitalized acute respiratory infections and impact of Haemophilus influenza immunization in a Tunisian university hospital: a twelve-year study. Issue 1 (1st January 2020) - Ben Fredj, Manel; Dhouib, Wafa; Kacem, Meriem; Bennasrallah, Cyrine; Mehrez, Ons; Abroug, Hela; Zemni, Imen; Gardabou, Aicha; Jamel, Koubaa; Chouchene, Slaheddine; Rouatbi, Naceur; Belguith Sriha, Asma
ABSTRACT: Background: We aimed to describe the episodes and trends of admissions for community-acquired Respiratory Infections (RI) over a 12-year period and to assess the impact of Haemophilus influenza type b (Hib) vaccine on RI admissions in children aged up to 3 years. Methods: We conducted a twelve-year retrospective observational study on all community-acquired RI admitted to Fattouma Bourguiba Hospital in Monastir Governorate (Tunisia) from 1 January 2002 to 31 December 2013. RI cases were selected from the Regional Registry of Hospital Morbidity. Data were coded according to ICD-10. To assess the impact of the Hib vaccine, three cohorts were defined based on vaccine status (unvaccinated cohort, first vaccinated cohort (VC) by monovalent form and second VC by pentavalent combination). Results: Admissions for RI represented 17.6% (CI95%: 17.3–18.1) of all communicable diseases hospitalizations (n = 6 061/34 289). The crude incidence rates (CIR) per 100, 000 inh were 24.2 for upper RI (URI) and 77.5 and for Lower RI (LRI) (p < 0.0001). Pneumonias represented 53.9% of LRI. Sex-ratio (male/female) was 1.12 for URI and 1.64 for LRI (p < 0.0001). At admission, the median age was 22 years (IQR: 3–52). Admission for Pneumonia increased significantly during study period (slope 'b' = 5.16; p < 0.0001) especially in children up to 5 years old (slope 'b' = 5.53) and in elderly (slope 'b' = 2.13). Among children up to 3 years old, the CIRs per 100, 000 for Hib pneumonia admission were 11.6 in Non-Vaccinated Cohort (NVC), 10.6 in Vaccinated Cohort (VC) by protocol 1 (Hib Vaccine monovalent) and 0.80 in VC by protocol 2 (pentavalent vaccine combination).The relative risk reduction was 99% for protocol 2 (p < 0.001). Conclusion: Admissions for RI in a  tertiary level hospital were common with an increasing trend. The Hib immunization program, in particular the pentavalent combination, has had a positive impact on the reduction of related acute diseases.